2012
DOI: 10.7771/1932-6246.1129
|View full text |Cite
|
Sign up to set email alerts
|

Is Insight Always the Same? A Protocol Analysis of Insight in Compound Remote Associate Problems

Abstract: Abstract:Compound Remote Associate (CRA) problems have been used to investigate insight problem solving using both behavioral and neuroimaging techniques. However, it is unclear to what extent CRA problems exhibit characteristics of insight such as impasses and restructuring. CRA problem-solving characteristics were examined in a study in which participants solved CRA problems while providing concurrent verbal protocols. The results show that solutions subjectively judged as insight by participants do exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
58
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 37 publications
9
58
1
2
Order By: Relevance
“…Although Mednick first created the RAT to require broad activation and retrieval of distant associations, the present study adds to a number of other studies that have shown that RAT items may actually be solved either via more or less analytic approaches (see for example Cranford & Moss, 2012). It may certainly be the case that RAT problem solving can…”
Section: Discussionsupporting
confidence: 49%
“…Although Mednick first created the RAT to require broad activation and retrieval of distant associations, the present study adds to a number of other studies that have shown that RAT items may actually be solved either via more or less analytic approaches (see for example Cranford & Moss, 2012). It may certainly be the case that RAT problem solving can…”
Section: Discussionsupporting
confidence: 49%
“…In other words, if individuals retrieve incorrect solutions initially, further work will often lead to repeated retrieval of the incorrect solutions, making it harder to think of new solutions. Such results have been shown in protocol studies (Cranford & Moss, 2012;Moss, Kotovsky, & Cagan, 2011).…”
Section: Problem Solving and The Persistence Of Fixationsupporting
confidence: 71%
“…Only problems correctly solved were analyzed (participants also provided incorrect solutions on an additional 10.2 % [SD=9.9 %] of the trials; 22.1 % [SD=24.5 %] of the incorrect solutions were labeled as insights). For the preparation period, we analyzed all problems solved in more than 2 s, since these are thought to accurately reflect both insight and analytic solving (e.g., Cranford & Moss, 2012). For the onset and solution periods, to avoid any overlap across the two analysis periods (2 s each), we analyzed just those problems solved in more than 4 s (M=70.7 %, SD=13.6 %, of all solutions).…”
Section: Resultsmentioning
confidence: 99%